أثر التجارة الالكترونية على مهنة المراجعة - زين, يونس; كشرود, بشير (جامعة الوادي - University of Eloued, 2013)
تواجه مهنة المراجعة تحديات جديدة أمام التطور التقني للمعلومات والنمو المسارع في تقنية الأعمال الالكترونية، وفيما يتعلق بنشر القوائم المالية على الانترنت مما يؤدي إلى أضعاف الثقة في البيانات المالية، ومن هذه التحديات: - لجوء الشركات إلى نشر قوائم مالية غير مدققة في مواقعها على الانترنت أو الربط بين بياناتها المالية المدققة وغير المدققة على الانترنت مما يؤدي إلى تضليل لمستخدمي القوائم المالية في اتخاذ قراراتهم . - تعرض البيانات المالية المنشورة على الانترنت والمدققة للتلاعب والتغيير من قبل صاحب المنشاة - التلاعب أو التغيير من قبل أطراف أخرى بسبب عدم تامين الموقع الالكتروني . ولذلك كان للانتشار الالكتروني المتزايد للقوائم المالية على الانترنت أثرا واضحا على تفعيل الهيئات المحاسبة المهنية الدولية لمواجهة التحديات من خلال قيامها بتعديل وتكييف القوانين والمعايير المهنية لتلاؤم مع التغيرات والتطورات في تقنية المعلومات الحديثة. Audit profession faced new challenges to the sophistication of the information and growth in e-business technology, and regarding the publication of the financial statements on the Internet, leading to fold confidence in the financial statements, and these challenges: - The companies resorting to publish unaudited financial statements in their Web sites or the link between their financial statements audited and unaudited online leading to mislead users of financial statements in making their decisions - The financial statements posted on the Internet and audited to manipulate and change by the owner of the facility - Manipulation or alteration by third parties due to lack secure Website. Therefore, it was to address the increasing spread of the financial statements on the Internet had a clear impact on activating the professional accountancy bodies to meet the challenges through its amending and adapting laws and professional standards for compatibility with the changes and developments in the modern information technology.
مقال
Keywords: التجارة الاكترونية، المراجعة، تكنولوجيا المعلومات.; Electronic Commerce, Auditing, Information Technology.